Poverty Among the Elderly: The Role of Public Pension Systems - Philippe Jacques; Marie-Louise Leroux; Dalibor Stevanovic (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
The objective of this paper is to measure the impact of first-pillar public pensions spending on the prevalence of poverty among the elderly. Using data from 27 European countries from 1995 to 2014, we estimate the elasticity of the poverty rate among individuals aged over 65 years to per capita public pension spending. We show the existence of a nonlinear relationship between these two variables. The elasticity is negative and statistically different from 0 only beyond a level of spending of 685 e per capita. At the average value of 2,819e, it is estimated that the elasticity is about -1.45. This nonlinear relation is robust to the treatment of possible endogeneity and to different robustness checks like the variation of the poverty line, and the inclusion of country-specific differences in public pension plans.
Keywords: 330